Effect of Different Dietary Carotenoids on Total Carotenoid Concentration and TBARS During Frozen Storage Rainbow Trout Flesh - Mehmet Emin Erdem; Nihat Yeşilayer; Nilgün Kaba (Journal of New Results in Science)
– In present study, thiobarbituric acid (TBARS) properties (mg malonaldehyde kg-1) in rainbow trout (Oncorhynchus mykiss) fed with standard diets supplemented with canthaxanthin, astaxanthin and red pepper meal besides control group were investigated. In experiment, total of 375 rainbow trout with an initial average weight of 154 g were fed by dividing into 4 groups. The fishes were fed for 60 days with four diets (canthaxanthin70 mg kg-1, astaxanthin 50 mg kg-1, red pepper meal 765 mg kg-1 and control). After the feeding period, the fishes in diet groups were evaluated in terms of total carotenoid concentration and TBARS. At the end of the trial, fodder supplemented with canthaxanthin, astaxanthin and red pepper meal caused carotenoid accumulation over 6 mg kg-1 concentration in the muscle tissues of the fishes. Frozen storage (at -30 ºC) of gutted, cleaned and glazed raw fishes for 12 months significantly reduced the total carotenoid concentration and TBARS value